Journal of the American Association of University Teachers of Insurance
Vols. 4-9, 13-22 comprise: Proceedings of the 4th-19th annual meetings, held 1933-1941, 1946-1954; Vol. 23 includes: Proceedings of the 20th annual meeting, 1955. No meetings were held 1942-45; two meetings held in 1947.